Changes in environment cause dietary shifts in the Svalbard Arctic fox: A stable isotope study - Krogh, Daniel J. (UiT Norges arktiske universitet, 2022)
In this thesis, shift in diet of Arctic foxes on Svalbard over a long time frame was analyzed. The Svalbard Arctic fox is a generalist who links the terrestrial and marine ecosystems. The objectives were 1) investigate whether there are spatial and temporal trends in Arctic fox diet on Svalbard, 2) determine how important the changes in the environmental variables are for dietary shifts of the Arctic fox in different seasons and 3) determine whether other parameters like the distance to the coast and age class have any impact on the diet as inferred from stable isotopes. Stable isotope values of carbon and nitrogen from Arctic fox muscle (representing winter diet) and fur (representing autumn diet) samples over the winter seasons 1997/1998 to 2019/2020 were used to assess dietary shifts. Arctic fox isotope values fitted mainly linearly between marine and resident terrestrial prey (reindeer and ptarmigan). Both negative temporal trends and differences between regions were found, signifying a shift towards more use of terrestrial resources in both winter and autumn. This was also found when analyzing environmental effects, where the number of geese and year to year fluctuations in reindeer carcass number were significant in shifting diet towards more use of terrestrial resources in winter. The distance to the coast also showed significant difference in the diet between coastal and inland Arctic foxes. The value of long time data series was shown in this thesis as these gave significant results, while short time data series usually did not. Continued monitoring and sampling, as well as including other parameters like seabird population estimates and the fox’s preference of marine invertebrates are of interest to improve models and give more accurate estimates.